1996
DOI: 10.1111/j.1467-6427.1996.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Too close or too separate: family function in families with an anorexia nervosa patient in two Nordic countries

Abstract: Previous research has shown that families with an anorexia nervosa patient are not a homogenous group. The purpose of this study was to see in what way these families differ from each other. Forty-nine families with a child suffering from anorexia nervosa were examined. They were rated by independent observers who, on the basis of a videotaped family task, evaluated family interaction using Beavers-Timberlawn's rating schedule. Family members completed the self-rrport questionnaires Family Climate, FARS and SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The first is that AN families (without reaching pathological levels of distance) felt more disengaged than NC families and expressed a higher level of dissatisfaction with what they considered insufficient connectedness. In light of some findings based on a modified version of the FACES (Wallin et al, 1996), which noted that anorexic patients from distant or 'centrifugal' families may have a worse prognosis than patients from close or 'centripetal' families, this notion of greater disengagement has important clinical and therapeutic implications. Those members who perceive family relationships as particularly distant need to be identified and contributing factors should be addressed in therapy.…”
Section: Discussion and Therapeutic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is that AN families (without reaching pathological levels of distance) felt more disengaged than NC families and expressed a higher level of dissatisfaction with what they considered insufficient connectedness. In light of some findings based on a modified version of the FACES (Wallin et al, 1996), which noted that anorexic patients from distant or 'centrifugal' families may have a worse prognosis than patients from close or 'centripetal' families, this notion of greater disengagement has important clinical and therapeutic implications. Those members who perceive family relationships as particularly distant need to be identified and contributing factors should be addressed in therapy.…”
Section: Discussion and Therapeutic Implicationsmentioning
confidence: 99%
“…From an empirical point of view, numerous investigations have been conducted over the last 15 years on the 'psychosomatic family' and its links with eating disorders. Overall, they have yielded inconsistent results (for a review of the literature, see Eisler, 1995;Humphrey, 1992), although two interesting trends have emerged from the data: (1) while there seems to be no specific pattern of family functioning associated with eating disorders (Dare, LeGrange, Eisler, & Rutherford, 1994;Rastam & Gillberg, 1991), eating-disordered families generally tend to be more dysfunctional than control families (Kog, Vertommen, & Vandereycken, 1987;Wallin, Roijen, & Hansson, 1996); and (2) the quality of family functioning plays a significant part in the course and outcome of the disorder (LeGrange, Eisler, Dare, & Russell, 1992;North, Gowers, & Byram, 1997;Strober, Freeman, & Morrell, 1997;Wewetzer, Deimel, Herpertz-Dahlmann, Mattejat, & Remschmidt, 1996). Important theoretical, diagnostic and methodological differences, which limit comparisons between studies, have been further complicated by an epistemological debate regarding who, the clinician or the family, holds the 'most realistic' perception of the anorexic family's interactional style.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy for the clinician to reach the conclusion that this lack of flexibility in family interaction is an inherent part of the family make up contributing to the aetiology of the eating disorder (Minuchin et al, 1978). While this may be the case for particular families, there is little evidence that families with someone with an eating disorder tend to be rigid in general or that how the eating disorder symptoms evolve is determined by the degree of flexibility/rigidity in the family (Dare et al, 1994;Wallin et al, 1996). Interestingly, when family members are asked to rate both how they perceive their family and how they would like their family to be, sufferers as well as other family members nearly universally expressed a wish for a greater degree of flexibility regardless of how flexible they perceive their family actually to be (Dare et al, 1994).…”
Section: Restriction Of the Available Patterns Of Family Interaction mentioning
confidence: 97%
“…These terms resemble the 'centrifugal' and 'centripetal' family styles and functions in Beavers-Timberlawn's rating scales (Beavers & Hampson, 1990;Beavers, 1989). Using this model, Wallin (Wallin, Røijen, & Hansson, 1996) examined a sample from Nordic countries and concluded that families with an anorectic child could be divided into three groups: centripetal, centrifugal and balanced. Clinical observations from individual or family therapy and other studies using different methodologies revealed similar results.…”
Section: Introductionmentioning
confidence: 99%